Factional Terror, Paramilitarism and Civil War in Haiti: The View from Port-au-Prince, 1994-2004 - Kovats-Bernat, J. Christopher (Anthropologica, 2022)
Twelve years after a United Nations invasion of the country, civil violence in Haiti has escalated to unprecedented proportions as local politics have again devolved into a street fight over vacuums of power left by failed constitutional processes. The instability of the government and the ongoing violent aftermath of a rebel uprising that began in February 2004 has transformed the capital of Port-au-Prince into a war zone, where civilians caught in the crossfire are modifying their social relations to the state and to one another in the interest of individual and community survival. This paper constructs a theoretical model for studying the current civil war in Haiti and calls for a deep ethnographic exploration of the violence, one that draws on a comprehensive political history, social analysis and cultural contextualization in assessing changing relations between the state and the civil society since the end of the Cedras coup d'etat in 1994.